THE EFFECT OF USING SCANNING TECHNIQUE ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSIO AT SMA IMELDA MEDAN - Azizah Husda (English Language Teaching Prima Journal (ELT), 2019)
Abstract This research investigates the effect of using Scanning Technique on Students’ Achievement in Reading Comprehension. The objective of the study is to find out the significant effect of using Scanning Technique on Students’ Achievement in Reading Comprehension. This research was conducted in three steps (pre-test, treatment. Post-test). The instrument for collecting data was multiple choice test. After the data had been collected, they were analyzed by using t-test formula in order to see whether Scanning Technique significantly effects students’ reading comprehension. The result of the analysis showed that t-observed was 3,36, it was higher than t-table 1,67 with the level of significant (0,05) and the degree of freedom (df) 52. The result of the analysis showed that hypothesis of the research was accepted. It means that there was significant effect of using Scanning Technique on Students’ Achievement in Reading Comprehension. Keywords: Reading Comprehension, Scanning Technique